Composite and interior material for vehicle, vehicle part, seat comprising the same

CN122910348APending Publication Date: 2026-10-13TORAY INDUSTRIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580019675.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-25
Filing Date
2025-03-12
Publication Date
2026-10-13

AI Technical Summary

Benefits of technology

[0033]通过本发明,可获得无色花、除了良好的表面品质或手感之外、强度或阻燃性能也优异的复合体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122910348A_ABST
    Figure CN122910348A_ABST
Patent Text Reader

Abstract

The present invention provides a sheet material having no color flower, and having both good surface quality or hand feeling and strength or flame retardant property. The present invention relates to a composite in which an artificial leather and a woven fabric a are adjacently laminated, and in the composite, the artificial leather includes a fiber structure having a base material composed of ultrafine fibers as a constituent member, and a high molecular elastomer, the woven fabric a includes a modified polyacrylonitrile fiber, and an adhesive resin is dispersed between the artificial leather and the woven fabric a.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a composite material made of artificial leather and woven fabric layered adjacent to each other. Background Technology

[0002] Artificial leather, primarily composed of fibrous structures containing extremely fine fibers and high-molecular elastomers, offers superior durability and more uniform quality compared to natural leather. Therefore, it is used in various fields such as vehicle interior materials, interior decoration, footwear, and clothing. When used in vehicle seats or furniture, artificial leather requires not only good surface quality and feel but also strength and flame retardancy as desirable characteristics.

[0003] Various solutions have been proposed to give artificial leather strength or flame-retardant properties. For example, Patent Document 1 proposes a flame-retardant artificial leather characterized by imparting a flame-retardant resin composition to artificial leather comprising a thermoplastic synthetic fiber fabric including woven, knitted, or nonwoven fabric and a polymeric elastomer impregnated therein. The flame-retardant resin composition comprises ammonium polyphosphate that has undergone water-hardening treatment, a triazine flame retardant with a specific range of water solubility, and an adhesive resin. Furthermore, it is described that the manufacturing method described in Patent Document 1 provides excellent flame retardancy without compromising the original soft feel of the artificial leather, suppresses the formation of color variations (which will be discussed later), exhibits excellent color variation resistance, and suppresses discoloration of the resin composition even when exposed to high temperatures, demonstrating excellent heat resistance.

[0004] Furthermore, Patent Document 2 discloses a flame-retardant leather sample substrate, characterized in that, in the leather sample substrate comprising a nonwoven fabric formed by three-dimensional entanglement of ultrafine fibers and a polymeric elastomer, at least a portion of the ultrafine fibers comprises an organophosphorus copolyester, and the polymeric elastomer comprises a polycarbonate-based polyurethane copolymerized from the organophosphorus components. Moreover, it is described that by adopting the aforementioned structure, it is halogen-free, exhibits excellent flame retardancy, and the durability of the flame retardancy is also extremely excellent.

[0005] Furthermore, Patent Document 3 proposes an artificial leather comprising a nonwoven fabric with interwoven polyester shrink fibers, potentially crimped fibers, and meta-type polyaramid fibers, each exhibiting significant shrinkage and crimp. The apparent density is within a specific range. The artificial leather is characterized by a specific content of each fiber. It is described that by adopting this structure, its feel and flame retardancy are significantly improved compared to existing artificial leathers with the same apparent density.

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-227685

[0009] Patent Document 2: Japanese Patent Application Publication No. 2002-201574

[0010] Patent Document 3: Japanese Patent Application Publication No. 2008-133578 Summary of the Invention

[0011] The problem that the invention aims to solve

[0012] Furthermore, as a technique for imparting flame-retardant properties to artificial leather, it is known that a method is to apply a water-soluble flame retardant, such as guanidine phosphate, to the entire artificial leather. However, the following problems exist: the smooth feel of the pile on the surface of the artificial leather is lost, or when the artificial leather absorbs moisture and dries, the guanidine phosphate dissolves and transfers to the surface due to the moisture, resulting in the formation of ring-shaped stains, the so-called "color spots," thus significantly impairing the design of the artificial leather.

[0013] According to the technology proposed in Patent Document 1, artificial leather that maintains a smooth surface quality while being less prone to color variations and possessing certain flame-retardant properties can be obtained. However, since a flame-retardant resin composition containing an adhesive resin is applied, there is room for improvement in the feel or drape of the artificial leather.

[0014] On the other hand, in the technology proposed in Patent Document 2, in order to give artificial leather strength and feel, the polymer elastomer, which is an important component, is polyurethane copolymerized with organophosphorus components. Therefore, compared with ordinary polymer elastomers, it becomes a design that reduces the feel and durability.

[0015] Furthermore, in the technology proposed in Patent Document 3, the artificial leather is made by blending various fibers, including polyester fibers and meta-aramid fibers, which makes it difficult to perform uniform napping or dyeing processes, resulting in uneven surface quality.

[0016] Therefore, the present invention is made in view of the above circumstances, and its object is to provide a sheet material that is free of color spots, has good surface quality or feel, and strength or flame retardant properties.

[0017] Technical means to solve the problem

[0018] To achieve the aforementioned objective, the inventors conducted repeated research and discovered that by producing a composite material in which artificial leather is laminated with a woven fabric containing specific flame-retardant fibers, and in which adhesive resin is discretely present between the layers of the artificial leather and the woven fabric, a composite material that not only has good surface quality or feel but also strength or flame-retardant properties can be obtained.

[0019] This invention is based on these insights and provides the following invention.

[0020] [1] A composite material is formed by adjacently layering artificial leather and woven fabric a, wherein,

[0021] The artificial leather comprises:

[0022] Fiber structures comprising a substrate made of extremely fine fibers as structural components; and

[0023] Polymer elastomers,

[0024] The woven fabric a comprises modified polyacrylonitrile fibers.

[0025] Adhesive resin is discretely present between the layers of the artificial leather and the woven fabric a.

[0026] [2] According to the composite described in [1], wherein the polyester fiber content in the woven fabric a is 5% by mass or more and 50% by mass or less.

[0027] [3] According to the composite described in [1] or [2], wherein the content of modified polyacrylonitrile fiber in the composite is 20% by mass or more and 50% by mass or less.

[0028] [4] The composite according to any one of [1] to [3], wherein the fibrous structure further comprises a braided fabric b.

[0029] [5] An interior material for a vehicle, comprising a composite according to any one of [1] to [4].

[0030] [6] A vehicle part comprising a composite according to any one of [1] to [4].

[0031] [7] A seat comprising the composite according to any one of [1] to [4].

[0032] The effects of the invention

[0033] Through this invention, a composite material with no color bloom, excellent surface quality or feel, and superior strength or flame retardant properties can be obtained. Attached Figure Description

[0034] [ Figure 1 ] Figure 1 This is a cross-sectional view of artificial leather illustrating and explaining the method for measuring and calculating the pile length of the artificial leather composite of the present invention.

[0035] [ Figure 2] Figure 2 This is a perspective concept diagram illustrating and explaining one embodiment (in a dotted configuration) of the adhesive resin of the composite of the present invention.

[0036] [ Figure 3 ] Figure 3 This is a perspective concept diagram illustrating and explaining one embodiment (in a lattice-like configuration) of the adhesive resin of the composite of the present invention.

[0037] [ Figure 4 ] Figure 4 This is a perspective concept diagram illustrating and explaining one embodiment (in a striped configuration) of the adhesive resin of the composite of the present invention.

[0038] [ Figure 5 ] Figure 5 This is a perspective concept diagram illustrating and explaining one embodiment of the adhesive resin of the composite of the present invention (in a state of random mesh configuration).

[0039] [ Figure 6 ] Figure 6 This is a perspective concept diagram illustrating and explaining the morphology of an adhesive resin that is not part of the present invention (a state in which adhesive resin is substantially present on the entire surface).

[0040] [ Figure 7 ] Figure 7 This is a perspective concept diagram illustrating and explaining the morphology of an adhesive resin that is not part of the present invention (a state in which it is disposed only at the end of the woven fabric a).

[0041] [ Figure 8 ] Figure 8 This is a perspective concept diagram illustrating and explaining the morphology of an adhesive resin that is not a composite of the present invention (a state in which it is only partially disposed in a part of the woven fabric a). Detailed Implementation

[0042] The composite of the present invention is a composite formed by adjacently layering artificial leather and woven fabric a, wherein the artificial leather comprises a fibrous structure containing a substrate made of extremely fine fibers as a constituent component and a polymeric elastomer, the woven fabric a comprises modified polyacrylonitrile fibers, and an adhesive resin is discretely present between the layers of the artificial leather and the woven fabric. These constituent components will be described in detail below, but the present invention is not limited to the scope of the following description as long as it does not depart from its spirit, and various modifications can be made without departing from the spirit of the present invention.

[0043] Furthermore, in this invention, the term "woven fabric" is a general term encompassing both machine-made and knitted fabrics.

[0044] [Substrate composed of ultra-fine fibers]

[0045] First, the artificial leather of the composite of the present invention comprises a fibrous structure, and the fibrous structure comprises a substrate made of extremely fine fibers as a constituent component.

[0046] The ultrafine fibers preferably contain a thermoplastic resin. As the thermoplastic resin, resins that can form fibers, such as polyester resins (e.g., polyethylene terephthalate, polybutylene terephthalate, and polyester elastomers), polyamide resins (e.g., polyamide 6, polyamide 66, and polyamide elastomers), polyurethane resins, polyolefin resins, and acrylonitrile resins, can be used. However, from the viewpoint of durability, especially mechanical strength and heat resistance, polyester resins are preferred. Furthermore, in this invention, "polyester resin" refers to a resin in which the polyester unit accounts for 80 mol% to 100 mol% of the molar fraction in the repeating unit. Unless otherwise specified, the use of the term "…resin" is the same.

[0047] Examples of the polyester resins include polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), polytetramethylene terephthalate (PTT), polycyclohexyldimethyl terephthalate (PTT), polyethylene-2,6-naphthalenedicarboxylate (2,6-naphthalenedicarboxylate), and polyethylene-1,2-bis(2-chlorophenoxy)ethane-4,4'-dicarboxylate. Preferably, the most commonly used polyethylene terephthalate or polyester copolymers primarily comprising polyethylene terephthalate units are used.

[0048] In the thermoplastic resin, inorganic particles such as titanium dioxide particles, lubricants, heat stabilizers, ultraviolet absorbers, conductive agents, heat storage agents, and antibacterial agents may be added as needed, without hindering the purpose of the present invention. In particular, when the artificial leather is to be dark in color, it is preferable to include black pigments such as carbon black and / or colored pigments such as nickel titanium yellow in the thermoplastic resin constituting the ultrafine fibers.

[0049] Furthermore, in this invention, "ultrafine fiber" refers to a fiber with a single fiber diameter of 15.0 μm or less, and preferably, the ultrafine fiber has an average single fiber diameter of 0.1 μm or more and 10.0 μm or less. By preferably having an average single fiber diameter of 0.1 μm or more, and more preferably 0.5 μm or more, a composite material exhibiting excellent color development, lightfastness, rubbing fastness, and stability during spinning after dyeing is achieved. On the other hand, by preferably having a diameter of 10.0 μm or less, and more preferably 8.0 μm or less, a composite material with a dense texture and soft feel exhibiting excellent surface quality is achieved.

[0050] Furthermore, in this invention, the average single fiber diameter of the so-called ultrafine fiber is determined and calculated by the following method.

[0051] (i) Take scanning electron microscope (SEM) images (e.g., "VHX-D500 / D510" manufactured by KEYENCE) images of the cross-section of the artificial leather in the composite section, and randomly select 10 extremely fine fibers that are considered to be circular or nearly circular elliptical (appearing to be fibers less than 15.0 μm in appearance) to determine the diameter of a single fiber. However, when determining the diameter of a single fiber, if it exceeds 15.0 μm, the fiber is not an extremely fine fiber, so another extremely fine fiber is selected and its diameter is determined.

[0052] (ii) Calculate the arithmetic mean of the diameters of the 10 single fibers and round it to the second decimal place.

[0053] From the viewpoint that the microfiber cross-sectional shape of the present invention can easily and stably form artificial leather microfibers during the composite manufacturing stage, and to create a composite with an excellent balance of quality, feel, and strength, a circular cross-section is preferred. However, depending on the required characteristics of the composite, irregular cross-sectional shapes such as elliptical, flat, triangular, polygonal, fan-shaped, cross-shaped, hollow, Y-shaped, T-shaped, and U-shaped cross-sections may also be used. In this case, the average single fiber diameter of the microfiber is determined by first measuring the cross-sectional area of ​​the single fiber and calculating the diameter when the cross-section is considered circular, thereby obtaining the diameter of the single fiber.

[0054] The substrate of the present invention is composed of the aforementioned ultrafine fibers. Such a substrate can take various forms, including nonwoven fabrics, woven fabrics, and forms that combine both, and can be appropriately differentiated according to the cost and characteristics required for each application or purpose.

[0055] The substrate is preferably a non-woven fabric. Using this substrate, a composite material with a substantial feel or excellent quality based on fine, raised fibers is achieved, even when the surface of the artificial leather is napped.

[0056] When the substrate is a nonwoven fabric, the nonwoven fabric can be in the form of a long-fiber nonwoven fabric mainly composed of filaments or a short-fiber nonwoven fabric mainly composed of fibers less than 100 mm. When the nonwoven fabric is a long-fiber nonwoven fabric, it becomes a composite with excellent strength, and is therefore preferred. On the other hand, when it is a short-fiber nonwoven fabric, compared to a long-fiber nonwoven fabric, more fibers can be oriented along the thickness direction of the artificial leather, thus creating a composite with a high degree of density on the surface when the artificial leather is napped.

[0057] When using short-fiber nonwoven fabric, the fiber length of the ultrafine fibers is preferably 25 mm or more and 90 mm or less. By limiting the upper limit of the fiber length range to 90 mm or less, more preferably 80 mm or less, and even more preferably 70 mm or less, a composite with good quality and hand feel is obtained. On the other hand, by limiting the lower limit of the fiber length range to 25 mm or more, more preferably 35 mm or more, and even more preferably 40 mm or more, a composite with excellent abrasion resistance is obtained.

[0058] Alternatively, it is preferable to include a woven fabric composed of the aforementioned ultrafine fibers as a constituent component. By using such a fibrous structure, a composite with excellent uniformity in thickness or quality can be produced.

[0059] [Fiber Structures]

[0060] Furthermore, the fibrous structure of the present invention includes a substrate made of the extremely fine fibers as a constituent component.

[0061] Furthermore, it is also preferable that the fiber structure further includes a woven fabric b. Specifically, the woven fabric b is laminated on the interior or one side surface of the substrate. Especially when the composite has an opening, if the woven fabric b is a woven fabric, it becomes a composite that can guarantee strength, and is therefore preferred. In addition, "the composite has an opening" means that there is a portion of the composite with an opening that extends through in the thickness direction (through opening). Moreover, the woven fabric b is different from the woven fabric a described later, and the woven fabric b is mainly composed of fibers other than modified polyacrylonitrile fibers. Here, "woven fabric mainly composed of fibers other than modified polyacrylonitrile fibers" means that the modified polyacrylonitrile fiber content in the fibers constituting the woven fabric is 1.0% by mass or less (including those that do not contain modified polyacrylonitrile fibers).

[0062] Furthermore, the type of fiber constituting the woven fabric b is preferably filament yarn, fine yarn, or a composite yarn of filament yarn and fine yarn. From the viewpoint of durability, especially mechanical strength, it is more preferable to use multifilament yarn containing polyester resin or polyamide resin.

[0063] The average single fiber diameter of the fibers constituting the woven fabric b is preferably set to 1 μm or more and 50 μm or less. By setting the upper limit of the range of the average single fiber diameter of the fibers to 50 μm or less, more preferably 15 μm or less, and even more preferably 13 μm or less, a composite with excellent softness is achieved. Furthermore, even when the fibers of the woven fabric b are exposed on the surface of the composite, the hue difference with the dyed, pigment-containing fine fibers is reduced, thus achieving a composite that does not compromise the uniformity of the surface hue. On the other hand, by setting the lower limit of the range of the average single fiber diameter of the fibers constituting the woven fabric b to 1 μm or more, more preferably 8 μm or more, and even more preferably 9 μm or more, a composite with high morphological stability is achieved.

[0064] In this invention, the average single fiber diameter of the fibers constituting the woven fabric b is set as a value determined and calculated by means of the following method: taking a scanning electron microscope (SEM, such as the "VHX-D500 / D510 type" manufactured by KEYENCE Corporation) photograph of the cross section of the composite, randomly selecting 10 fibers constituting the woven fabric b, measuring the single fiber diameter of the fibers and calculating the arithmetic mean of the 10 fibers, and rounding to two decimal places.

[0065] When the fibers constituting the woven fabric b are multifilaments, the total fineness of the multifilaments is preferably 30 dtex or more and 170 dtex or less. By limiting the upper limit of the total fineness range of the yarns constituting the woven fabric b to 170 dtex or less, a composite with excellent softness can be obtained. On the other hand, by limiting the lower limit of the total fineness range of the yarns constituting the woven fabric b to 30 dtex or more, not only is the morphological stability of the composite product improved, but also when the nonwoven fabric and the woven fabric b are entangled together using needle punching or the like, the fibers constituting the woven fabric b are less likely to be exposed on the surface of the composite, which is therefore preferable. In this case, the total fineness of the multifilaments of the warp and weft yarns is preferably set to be the same.

[0066] Furthermore, the total fineness of the yarns constituting the woven fabric b refers to the value measured and calculated by means of "8.3.1 Normal Fineness b) Method B (Simplified Method)" in "8.3 Fineness" of Japanese Industrial Standards (JIS) L1013:2010 "Test Methods for Chemical Fiber Filament Yarn".

[0067] In this case, the fiber structure of the present invention is preferably formed by the entanglement of the substrate and the woven fabric b. This type of fiber structure, especially when the composite has an opening, results in a composite with excellent strength or morphological stability. Furthermore, in the present invention, "the substrate and the woven fabric b are entangled in an integrated manner" refers to a state in which a plurality of extremely fine fibers constituting the substrate are entangled with fibers constituting the woven fabric b, and the substrate and the woven fabric b are integrated.

[0068] [Polymer Elastomers]

[0069] The artificial leather of the composite of the present invention contains a polymer elastomer. Here, in the present invention, "containing a polymer elastomer" means that the remaining central 40% of the artificial leather in the composite, after removing 30% of the portion in the thickness direction from the two surfaces other than the pile portion, contains a polymer elastomer, which can be determined by the process shown in (1) to (7) below.

[0070] (1) Using a lint brush or similar tool, the raised surface of the artificial leather is bent down, and in the state described, a thin slice with a thickness of 1 mm is made from a randomly selected position in the artificial leather along the thickness direction of the artificial leather.

[0071] (2) Observe the central 40% of the section of the thin section of (1) by scanning electron microscope (SEM, such as the “VHX-D500 / D510” manufactured by Keyence Corporation).

[0072] (3) In the SEM images taken, confirm whether there are any substances other than fibers that constitute the fibrous structure.

[0073] (4) In the presence of substances other than the fibers constituting the fibrous structure, the substances coated on the surface of the artificial leather are removed by peeling or other means.

[0074] (5) After removing 30% of the artificial leather from the two surfaces other than the pile portion in the thickness direction, only the central 40% remains.

[0075] (6) Dissolve the test piece from (5) in N,N-dimethylformamide (DMF) and hexafluoroisopropanol (HFIP). Perform compositional analysis on the solute in the dissolved DMF solution and the insoluble matter in HFIP to confirm the presence or absence of polymeric elastomers. Then, in the compositional analysis, for example, confirm the presence or absence of polymeric elastomers by infrared spectroscopy (IR).

[0076] (7) Either the solute in the DMF solution or the insoluble matter of HFIP is considered to contain a polymeric elastomer if the structure of the polymeric elastomer described later can be confirmed.

[0077] The polymeric elastomer is an adhesive that binds the extremely fine fibers that constitute the artificial leather. Therefore, considering the soft feel of the composite of the present invention, polyurethane is preferably used as the main component of the polymeric elastomer. Furthermore, the term "main component" as used in the present invention refers to polyurethane having a mass greater than 50% by mass relative to the total mass of the polymeric elastomer.

[0078] In this invention, the polyurethane preferably used as a polymeric elastomer can be either an organic solvent-based polyurethane used in a dissolved state or a water-dispersible polyurethane used in a dispersed state in water. Here, in this invention, a water-dispersible polyurethane refers to a polyurethane having a hydrophilic group and a solubility in DMF of less than 40 g / 100 g-DMF (the polyurethane dissolves less than 40 g relative to 100 g of DMF). Conversely, an organic solvent-based polyurethane resin is defined as a polyurethane with a solubility in DMF of 40 g / 100 g-DMF or more (the polyurethane dissolves more than 40 g relative to 100 g of DMF).

[0079] In this invention, for the purpose of improving water resistance, abrasion resistance, and hydrolysis resistance, polyurethane used as a polymeric elastomer is preferably used in conjunction with a crosslinking agent. The crosslinking agent can be an external crosslinking agent added as a third component to the polyurethane, or an internal crosslinking agent that pre-introduces reaction sites within the molecular structure of the polyurethane to form a crosslinking structure. From the viewpoint that a uniform crosslinking point can be formed within the molecular structure of the polyurethane, thereby mitigating the reduction in flexibility, an internal crosslinking agent is more preferred.

[0080] In addition, polymeric elastomers may contain various additives depending on their purpose, such as flame retardants (phosphorus-based, halogen-based, and inorganic-based), antioxidants (phenol-based, sulfur-based, and phosphorus-based), UV absorbers (benzotriazole-based, triazine-based, benzophenone-based, salicylate-based, cyanoacrylate-based, and oxalic acid anilide-based), light stabilizers (hindered amine-based or benzoate-based), hydrolysis stabilizers (polycarbodiimide-based or oxazoline-based), plasticizers, antistatic agents, surfactants, coagulation modifiers, carbon black, and dyes.

[0081] Generally, the content of polymeric elastomers in artificial leather can be appropriately adjusted considering the type of polymeric elastomer used, the manufacturing method of the polymeric elastomer, and its feel or physical properties. In this invention, the content of polymeric elastomers relative to the mass of the artificial leather is preferably 2% by mass or more and 50% by mass or less. By limiting the lower limit of the range of the content of the polymeric elastomers to 2% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, the bonding between fibers based on polymeric elastomers can be strengthened during the artificial leather production stage, thus creating a composite with excellent strength. On the other hand, by limiting the upper limit of the range of the content of the polymeric elastomers to 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less, it not only creates a composite with a soft feel but also creates a composite that can suppress dye contamination of other fabrics washed at the same time.

[0082] Furthermore, in this invention, the proportion (mass%) of polymeric elastomer in the artificial leather is set as a value determined and calculated using the following process.

[0083] (1) Three test pieces of 10 cm × 10 cm were randomly collected from the complex.

[0084] (2) In the presence of a substance coated on the surface of the artificial leather in the composite, the layer is removed by peeling or the like.

[0085] (3) After removing 30% of the artificial leather from the two surfaces other than the pile portion in the thickness direction, only the central 40% remains.

[0086] (4) In the method (7) for confirming whether the polymeric elastomer is contained, if the structure of the polymeric elastomer can be confirmed on the solute side of the DMF solution, process (5) is performed; if the structure of the polymeric elastomer can be confirmed on the insoluble side of the HFIP, process (6) is performed, and the content ratio of the polymeric elastomer is calculated. In addition, if the structure of the polymeric elastomer can be confirmed on both DMF and HFIP, the larger value calculated in process (5) and process (6) is used as the content ratio of the polymeric elastomer.

[0087] (5) Immerse the test pieces in DMF and dry them at 25°C for 24 hours. Calculate the mass ratio of the test pieces before and after dissolution using the following formula. For the arithmetic mean (%) of the three test pieces, round off the first decimal place to calculate the proportion of polymer elastomer.

[0088] (Sample mass before dissolution (g) - Sample mass after dissolution and drying (g)) / (Sample mass before dissolution (g)) × 100 ··· (Equation)

[0089] (6) Immerse the test pieces in HFIP and dry them at 25°C for 24 hours. Calculate the mass ratio of the test pieces before and after dissolution using the following formula. Round the first decimal place of the arithmetic mean (%) of the three test pieces to obtain the percentage of polymer elastomer content.

[0090] (mass of the dissolved sample (g)) / (mass of the sample before dissolution (g)) × 100 ··· (formula).

[0091] [Artificial Leather]

[0092] The composite artificial leather of the present invention comprises the fibrous structure and the polymeric elastomer. Furthermore, in the composite artificial leather of the present invention, it is preferable that the surface not adjacent to the woven fabric a has pile, and further preferably, a surface resin layer is provided on the surface having pile.

[0093] That is, in this invention, the pile can be present only on the surface of the artificial leather that is not adjacent to the woven fabric a, as described above, or it is permissible to have it on both surfaces. From the viewpoint of design effect, when the pile is present on the surface that is not adjacent to the woven fabric a, the pile shape is preferably such that it has a pile length and directional softness to the extent that a fingerprint is left when a finger is stroked due to the change in the direction of the pile, i.e., fingerprints are produced.

[0094] More specifically, the surface pile length is preferably 200 μm or more and 500 μm or less. By having a lower limit of 200 μm or more, and more preferably 250 μm or more, the surface pile is covered by a polymer elastomer located inside the matrix, suppressing the exposure of the polymer elastomer on the side of the artificial leather that is not adjacent to the woven fabric a, thus creating a composite with uniform color rendering. Furthermore, when the woven fabric b is entangled and integrated with the nonwoven fabric constituting the artificial leather, by setting the surface pile length to the aforementioned range, the fibers of the woven fabric b located near the surface of the artificial leather can be sufficiently covered, which is therefore preferable. On the other hand, by having an upper limit of 500 μm or less, and more preferably 450 μm or less, a composite with excellent design effect and wear resistance is created.

[0095] In this invention, the pile length of artificial leather is determined and calculated by the following method.

[0096] (1) For a surface with raised nap, use a cotton brush or the like to turn the raised nap upside down.

[0097] (2) With the fur standing upside down, use a scanning electron microscope (SEM: such as the “VHX-D500 / D510” manufactured by Keyence Corporation) to take two cross-sections of the artificial leather at a magnification of 120x.

[0098] (3) such as Figure 1 As illustrated, the layer containing only fibers oriented in the thickness direction in the cross section is taken as the pile portion (2), and the length from the intersection of the fibers oriented in the thickness direction and the fibers oriented in the surface direction of the artificial leather to the front end of the pile is taken as the pile length (μm), and it is measured at 10 points.

[0099] (4) Repeat (3) for all sections to calculate the arithmetic mean of the standing hair length (μm) and round it to the nearest decimal place.

[0100] In this invention, when the surface resin layer is present, it may be a continuous layer (in which case the surface of the composite becomes a silver-toned surface) or a discontinuous layer (in which case the surface of the composite becomes a semi-silver-toned surface).

[0101] The surface resin layer preferably comprises one or more resins selected from the group consisting of styrene-butadiene rubber, nitrile rubber, acrylic resin, epoxy resin, polyurethane resin, and natural resin. From the viewpoint of flexibility and abrasion resistance, polyurethane resin is preferred.

[0102] In this invention, the resin used in the surface resin layer may contain, to a extent that does not impair the effects of this invention, elastomer resins such as polyester-based, polyamide-based, and polyolefin-based resins, acrylic resins, and ethylene-vinyl acetate resins. Furthermore, these resins may contain various additives, such as pigments like carbon black, flame retardants such as phosphorus-based, halogen-based, and inorganic-based resins, antioxidants such as phenolic, sulfur-based, and phosphorus-based resins, light stabilizers such as hindered amine-based or benzoic acid ester-based resins, hydrolysis-resistant stabilizers such as polycarbodiimide, plasticizers, antistatic agents, surfactants, coagulation modifiers, and dyes.

[0103] [Knitted fabric a]

[0104] The woven fabric a of the composite of the present invention comprises modified polyacrylonitrile fibers. The modified polyacrylonitrile fibers refer to fibers containing acrylonitrile with an acrylonitrile content of 35% by mass or more and less than 85% by mass. Furthermore, the modified polyacrylonitrile fibers generate an inert gas during combustion, which contributes to the self-extinguishing effect of the flame on the surface of the composite. The composite formed by laminating artificial leather adjacent to the woven fabric a containing the modified polyacrylonitrile fibers, with gaps between the fibers, and the artificial leather having a flammable structure, is not easily combustible.

[0105] Furthermore, the woven fabric a preferably also contains polyester fibers, which are preferably 5% by mass or more and 50% by mass or less. By having a lower limit of 5% by mass or more, and more preferably 10% by mass or more, the composite exhibits excellent strength. On the other hand, by having an upper limit of 50% by mass or less, and more preferably 45% by mass or less, the composite exhibits excellent flame-retardant properties.

[0106] Furthermore, the proportion of modified polyacrylonitrile fiber or polyester fiber in the woven fabric a is as follows: For the woven fabric a that remains after being peeled or ground from the composite except for the woven fabric a, the value is determined and calculated according to "Part 1: Fiber Identification" of JIS L1030-1:2012 "Test Method for Blending Rate of Fiber Products" and "Part 2: Fiber Blending Rate" of JIS L1030-2:2012 "Test Method for Blending Rate of Fiber Products" under "5 Unwinding Method" or "6 Dissolution Method".

[0107] The woven fabric a in the composite of the present invention can be, for example, plain weave fabric, twill weave fabric, satin weave fabric, and various woven fabrics based on these weaving structures, or warp-knitted fabric, weft-knitted fabric represented by Tricot warp-knitted fabric, lace fabric, and various knitted fabrics based on these weaving structures. Either woven fabric or knitted fabric is also permitted.

[0108] Among these considerations, taking into account the bonding strength with the artificial leather, the material strength of the woven fabric a, and the softness or flame retardant properties of the composite, it is preferable that the woven fabric a is a woven material. This results in a composite with excellent bonding strength between the artificial leather and the woven fabric a, as well as excellent softness or flame retardant properties.

[0109] [Complex]

[0110] The composite of the present invention is formed by adjacently layering artificial leather and woven fabric a. Furthermore, adhesive resin is discretely present between the layers of the artificial leather and the woven fabric a. Here, "adhesive resin is discretely present between the layers of the artificial leather and the woven fabric a" specifically refers to...

[0111] like Figure 2 The adhesive resin is arranged in a dotted pattern.

[0112] like Figure 3 The adhesive resin is arranged in a grid pattern.

[0113] like Figure 4 The adhesive resin is arranged in a striped pattern.

[0114] like Figure 5 The adhesive resin is arranged in a random mesh pattern.

[0115] etc., and refers to not

[0116] like Figure 6 That essentially creates a state where the entire surface is bonded with resin.

[0117] like Figure 7 That state, which is only configured at the end of the woven fabric a,

[0118] like Figure 8 That state, where it is only partially configured in a part of the woven fabric a

[0119] wait.

[0120] The adhesive resin of the present invention can be suitably selected from, for example, polyurethane, acrylic resin, silicone resin, polyolefin, polyamide, epoxy resin, vinyl chloride, polyester, etc., depending on the raw materials or form of the woven fabric a. Among these, polyurethane or acrylic resin is preferred when considering flexibility and adhesion at high temperatures. Polyurethane, which has high adhesion and high flexibility, is particularly preferred. Furthermore, the polyurethane is preferably a moisture-curing reactive hot melt adhesive, a two-component liquid type mixed with isocyanate or chain elongation agent.

[0121] The modified polyacrylonitrile fiber content in the composite is preferably 20% by mass or more and 50% by mass or less. By setting the lower limit of the modified polyacrylonitrile fiber content to 20% by mass or more, and more preferably 25% by mass or more, a composite with excellent flame-retardant properties is obtained. On the other hand, by setting the upper limit of the modified polyacrylonitrile fiber content to 50% by mass or less, and more preferably 45% by mass or less, a composite with excellent strength is obtained.

[0122] Furthermore, in this invention, the proportion of modified polyacrylonitrile fiber in the composite is as follows: the value determined and calculated according to "Part 1: Fiber Identification" of JIS L1030-1:2012 "Test Method for Blending Rate of Fiber Products" and "Part 2: Fiber Blending Rate" of JIS L1030-2:2012 "Test Method for Blending Rate of Fiber Products" using either the "5 Unwinding Method" or the "6 Dissolution Method".

[0123] The composite of the present invention is preferably 200 g / m². 2 Above and 900 g / m 2 The lower limit of the range of the mass per unit area of ​​the composite is preferably 200 g / m². 2 The above, and more preferably 250 g / m 2 The above, and more preferably, is 300 g / m 2 The above results in a composite material with a substantial feel and excellent tactile quality. Furthermore, the upper limit of the range of the mass per unit area of ​​the composite material is preferably 900 g / m². 2 The following, or more preferably, is 800 g / m 2 The following, and more preferably, is 700 g / m 2 The resulting material is a composite with excellent formability and flexibility.

[0124] Furthermore, in this invention, the mass per unit area of ​​the composite is determined and calculated using the following method.

[0125] (i) Three test pieces of 5 cm × 5 cm size were randomly collected from the complex.

[0126] (ii) Determine the mass of the complex to one decimal place.

[0127] (iii) Divide the mass of the composite by the area of ​​the test piece to calculate the mass per unit area of ​​each composite sample. The arithmetic mean (g / m²) of the three test pieces is then calculated. 2 Rounding is performed on the first decimal place.

[0128] The composite of the present invention preferably has a thickness of 0.2 mm or more and 5.0 mm or less, as measured by method 6.1.1A of "6.1 Thickness (International Organization for Standardization, ISO) Method" in JIS L1913:2010 "General Test Methods for Nonwoven Fabrics". By limiting the lower limit of the composite thickness to 0.2 mm or more, more preferably 0.3 mm or more, and even more preferably 0.4 mm or more, a composite exhibiting excellent processability during manufacturing, as well as a substantial feel and superior hand-feel. Conversely, by limiting the upper limit of the composite thickness to 5.0 mm or less, more preferably 4.5 mm or less, and even more preferably 4.0 mm or less, a composite exhibiting excellent formability and softness.

[0129] Furthermore, in this invention, the thickness of the composite is determined and calculated using the following method.

[0130] (i) Take ten 2500 mm images from the composite. 2 Test pieces of the above sizes (e.g., square test pieces of 50 mm × 50 mm, or circular test pieces of 60 mm in diameter, etc.).

[0131] (ii) Apply a pressure of 0.5 kPa to the upper circular horizontal plate of the thickness measuring instrument (such as the "H-1A" of the dial thickness gauge manufactured by Ozaki Corporation) and adjust the 0 point.

[0132] (iii) Using a thickness gauge, apply a pressure of 0.5 kPa to the test piece for 10 seconds and measure the thickness to 0.01 mm.

[0133] (iv) Calculate the arithmetic mean (mm) of the ten test pieces and round it to the third decimal place.

[0134] The composite of the present invention preferably has an average tensile strength of 100 N / 5 cm or more and 2000 N / 5 cm or more, measured by JIS L1913:2010 "General Test Methods for Nonwoven Fabrics" "6.3.1 Tensile Strength and Elongation (ISO Method)". If the average tensile strength is 100 N / 5 cm or more, more preferably 150 N / 5 cm or more, and even more preferably 200 N / 5 cm or more, the composite exhibits excellent morphological stability or durability, and is therefore preferred. Furthermore, if the average tensile strength is 2000 N / 5 cm or less, more preferably 1800 N / 5 cm or less, and even more preferably 1500 N / 5 cm or less, it becomes a composite with excellent formability.

[0135] Furthermore, the tensile strength can be adjusted by the unit area mass or density of the artificial leather, the density of the layered weave a or the inserted weave b, and the total fineness of the constituent threads.

[0136] Here, the composite of the present invention is preferably characterized by excellent flame retardancy, and is a qualified composite when evaluating the flame retardant performance of the composite below.

[0137] The flame retardant performance of the composite is evaluated based on the combustion test specifications (horizontal burning speed) for automotive interior materials according to the Federal Motor Vehicle Safety Standards (FMVSS) No. 302. A horizontal test piece (350 mm × 100 mm) is held in contact with a 38 mm flame for 15 seconds. The determination is based on the burning speed of 254 mm relative to the A mark to the B mark, according to the following criteria.

[0138] If the fire self-extinguishes before reaching the A mark, the judgment category will be set to "non-flammable" and the fire will be deemed qualified.

[0139] • If a fire self-extinguishes after exceeding the A mark, and the burning distance is within 50 mm and the burning time is within 60 seconds, the judgment will be set as "self-extinguishing" and the fire will be deemed qualified.

[0140] • If the burning rate between the markings is less than 80 mm / minute, even if it does not self-extinguish, the judgment will be set as "burning below the specified speed" and it will be deemed as qualified.

[0141] • If the fire does not self-extinguish and the burning speed between the markings exceeds 80 mm / minute, the judgment will be set as "burning at a speed exceeding the specified speed", and the fire will be deemed unqualified.

[0142] In addition, the flame retardant properties can be adjusted by the proportion of modified polyacrylonitrile fibers in the woven fabric a, or by the unit area mass of the artificial leather and the woven fabric a.

[0143] When the composite of the present invention is used in vehicle interior materials, it is particularly preferred to have multiple openings, especially for the purpose of high ventilation required for seat ventilation systems.

[0144] The term "opening" in this invention is not limited to portions where the composite opening has a hole (through opening) extending along the thickness direction. For example, it also includes cases where the openings of the artificial leather and the woven fabric a do not overlap in the planar direction and thus do not constitute through openings. As an example of the latter, a configuration in which an opening is pre-formed on the artificial leather and layered with the woven fabric a can be cited.

[0145] The shape of the opening can be any shape as desired, including circles, ellipses, flat and triangular polygons, fan shapes, cross shapes, hollow shapes, Y-shaped shapes, T-shaped shapes, and U-shaped shapes. The arrangement pattern of the openings is not particularly limited; they can be arranged regularly or irregularly. From the viewpoint of achieving uniform air permeability and strength throughout the composite, a regular arrangement at predetermined intervals is preferred. From the viewpoint of balancing the air permeability and strength of the composite, the aperture of the opening is preferably 0.1 mm or more and 3.0 mm or less; from the viewpoint of maintaining strength or morphological stability, the opening ratio is preferably 20% or less.

[0146] Furthermore, the "opening ratio" in this invention refers to the ratio of the area of ​​the opening to the area relative to the surface area of ​​the composite.

[0147] [Manufacturing method of laminated bodies]

[0148] The manufacturing method of the composite of the present invention preferably includes a step in which the adhesive resin is discretely present between the layers of the artificial leather and the woven fabric a. Details of these steps will be described below.

[0149] (1) Processes for forming artificial leather

[0150] Firstly, as a fibrous structure for artificial leather, methods for forming a substrate composed of extremely fine fibers include: a method of directly spinning fibers of the aforementioned average single fiber diameter to obtain the substrate; and a method of temporarily forming a sheet composed of fibers exhibiting extremely fine fiber characteristics (described later), and then forming the substrate from which extremely fine fibers of the aforementioned average single fiber diameter are exposed (method via a sheet composed of fibers exhibiting extremely fine fiber characteristics). Among these, from the viewpoint of being highly operable and obtaining fibers with uniform single fiber diameters, the method of temporarily forming a sheet composed of fibers exhibiting extremely fine fiber characteristics is preferred.

[0151] As a type of ultrafine fiber, a sea-island composite fiber is used where thermoplastic resins with different solvent solubility are used as the sea component (easily soluble polymer) and the island component (poorly soluble polymer). The sea component is removed by dissolving it with a solvent, thereby leaving the island component as a fiber with the average single fiber diameter. By using a sea-island composite fiber, a suitable gap can be provided between the island components, i.e., between the ultrafine fibers inside the fiber bundle, when the sea component is removed. Therefore, it is preferred from the viewpoint of the soft hand feel or surface quality of the composite.

[0152] From the viewpoint of obtaining ultrafine fibers with a uniform single fiber diameter, a method for spinning ultrafine fibers with an island-type composite structure is preferred, which involves using a die for island-type composite fibers to spin a polymer inter-arrangement in which the sea component and the island component are arranged in relation to each other.

[0153] As the sea component of island-type composite fibers, polyethylene, polystyrene, copolyesters copolymerized from sodium isophthalate sulfonate or polyethylene glycol, polylactic acid, polyvinyl alcohol and their copolymers can be used. However, from the viewpoint of yarn-making properties or easy dissolution, polystyrene or copolyesters are preferred.

[0154] When using the island-type composite fiber, it is preferable to set the strength of the island component to 2.0 cN / dtex or higher. By setting the strength of the island component to preferably 2.0 cN / dtex or higher, more preferably 2.3 cN / dtex or higher, and even more preferably 2.8 cN / dtex or higher, the abrasion resistance of the composite can be improved and the decrease in frictional fastness accompanying fiber shedding can be suppressed.

[0155] Furthermore, in this invention, the strength of the island component of the so-called island-type composite fiber is a value that is measured and calculated by the following method.

[0156] (1) Bundle 10 island-type composite fibers with a length of 20 cm.

[0157] (2) After dissolving and removing the marine components from the sample in (1), air dry.

[0158] (3) The test was conducted 10 times (N=10) under the conditions of clamping length 5 cm, stretching speed 5 cm / min and load 2 N, according to "8.5 Tensile strength and elongation" of JIS L1013:2010 "Test methods for chemical fiber filament yarn".

[0159] (4) The arithmetic mean (cN / dtex) of the experimental results obtained in (3) is rounded to two decimal places.

[0160] Here, when the substrate is a nonwoven fabric, the spun ultrafine fibers are opened and then formed into a fiber web using a cross-lapper or similar machine, and then entangled to obtain a fiber structure containing a nonwoven fabric as a component. As a method for obtaining a fiber structure containing a nonwoven fabric as a component by entanglement of the fiber web, needle punching or water jet punching can be used.

[0161] As described above, either short-fiber or long-fiber nonwoven fabric can be used for the nonwoven fabric. However, if it is short-fiber nonwoven fabric, there are more fibers in the thickness direction of the artificial leather than in long-fiber nonwoven fabric, which can achieve a high degree of density and a soft hand feel on the surface of the composite when it is napped.

[0162] When the nonwoven fabric is a short-fiber nonwoven fabric, the island-type composite fibers obtained in the process of forming the island-type composite fibers are preferably crimped, cut to a specified length to obtain raw cotton, and then opened, layered, and entangled to obtain the short-fiber nonwoven fabric. Known methods can be used for crimping and cutting.

[0163] When using short-fiber nonwoven fabric, the average fiber length of the ultrafine fiber-displaying fibers is preferably 25 mm or more and 90 mm or less. By setting the average fiber length to 90 mm or less, more preferably 80 mm or less, and even more preferably 70 mm or less, good quality and a soft hand feel are obtained. On the other hand, by setting the average fiber length to 25 mm or more, more preferably 35 mm or more, and even more preferably 40 mm or more, a composite with excellent abrasion resistance can be produced.

[0164] Furthermore, if the fiber structure also includes a woven fabric b as a component, a sheet made of ultrafine fiber-manifested fibers obtained by the method can be laminated with the woven fabric b, and then entangled together. When entangled together with the woven fabric b, the woven fabric b can be laminated on one or both surfaces of the sheet made of ultrafine fiber-manifested fibers, or the woven fabric b can be sandwiched between multiple sheets made of ultrafine fiber-manifested fibers, and then the fibers of the sheet made of ultrafine fiber-manifested fibers and the woven fabric b can be intertwined through needle punching or hydroentangling.

[0165] Preferably, the apparent density of the sheet composed of extremely fine, visible fibers after needle punching or hydroentangling (hereinafter referred to as "entangled sheet"; also including those entangled with the woven fabric b) is set to 0.15 g / cm³. 3 Above and 0.45g / cm 3 The following is an example. The apparent density is preferably set to 0.15 g / cm³. 3 In this way, even when excessive tension is applied during the manufacturing stage, the fibers are less likely to fall off or elongate, thereby obtaining a composite with improved fiber density and good appearance quality. On the other hand, by setting the apparent density to preferably 0.45 g / cm³... 3 The following can maintain sufficient space for imparting polymer elastomers, retain the voids in the cross section, thereby producing a composite with a soft feel.

[0166] To improve the density of the fibers, it is also preferable to perform heat shrinkage treatment on the entangled sheet using warm water or steam.

[0167] Next, the water-soluble resin can also be imparted by impregnating the entangled sheet with an aqueous solution of the water-soluble resin and then drying it. By imparting the water-soluble resin to the entangled sheet, the fibers are fixed and dimensional stability is improved. Here, in this invention, the term "water-soluble resin" refers to a resin that is soluble in water or hot water (i.e., water at 80°C to 100°C), specifically including polyacrylamide, polyvinyl alcohol, carboxymethyl cellulose, etc.

[0168] Subsequently, the obtained entangled sheet can be treated with a solvent or solution to reveal extremely fine fibers. One method for forming extremely fine fibers with an average single fiber diameter of 1.0 μm or more and 10.0 μm or less is the aforementioned treatment. Furthermore, the entangled sheet revealing extremely fine fibers will hereinafter be abbreviated as extremely fine fiber sheet.

[0169] The formation of the ultrafine fiber sheet using the method described above can be achieved by immersing the entangled sheet in a solvent or solution to dissolve and remove the marine components of the island-type composite fiber.

[0170] As solvents for dissolving and removing marine components, organic solvents such as toluene or trichloroethylene can be used when the marine component is polyethylene or polystyrene. Alternatively, alkaline aqueous solutions such as sodium hydroxide solution can be used when the marine component is copolyester or polylactic acid. Furthermore, hot water can be used when the marine component is water-soluble thermoplastic polyvinyl alcohol.

[0171] Furthermore, by impregnating a solution of the polymeric elastomer into a sheet of ultrafine fibers or an entangled sheet and then curing the polymeric elastomer, a sheet containing the polymeric elastomer can be formed. As a method for curing the polymeric elastomer, there are methods such as impregnating a solution of the polymeric elastomer into a sheet of ultrafine fibers or an entangled sheet and then performing wet curing or dry curing; these methods can be appropriately selected depending on the type of polymeric elastomer used.

[0172] When selecting polyurethane as the polymeric elastomer, N,N-dimethylformamide or dimethyl sulfoxide are preferably used as the solvent, especially when the polyurethane is an organic solvent-based polyurethane. Alternatively, when the polyurethane is a water-dispersible polyurethane, a water-dispersible polyurethane solution prepared by dispersing the polyurethane as an emulsion in water can also be used.

[0173] Furthermore, when a polymeric elastomer is imparted to the entangled sheet, it can be treated with a solvent or solution after the sheet with the polymeric elastomer is formed, thereby revealing extremely fine fibers. The specific process is the same as described above.

[0174] As described above, a sheet containing a fibrous structure with a substrate made of extremely fine fibers as a constituent component and a polymeric elastomer can be formed. This sheet can be directly transferred to subsequent processes as artificial leather, but alternatively, one surface of the obtained sheet can be ground to form artificial leather with a napped texture. From a manufacturing efficiency point of view, it is also preferable to cut the sheet in half along its thickness direction to produce two sheets of artificial leather before grinding the surface of the artificial leather.

[0175] Specifically, one of the surfaces of the sheet material (including half-cut sheets) can be sanded using sandpaper or a sander to form a synthetic leather with a napped texture. A lubricant such as a silicone emulsion can also be applied to the surface of the sheet material before sanding.

[0176] The material that has been completed up to the aforementioned steps can also be used directly as artificial leather, but it is preferable to produce artificial leather by performing various post-processing steps in the same way as the general method for manufacturing artificial leather. Of course, artificial leather that has undergone post-processing is also considered artificial leather in this invention.

[0177] Firstly, it is preferable to perform a dyeing treatment on the artificial leather. Examples of methods for performing this dyeing include: liquid dyeing using a jigger dyeing machine or a liquid dyeing machine; immersion dyeing using a thermosol dyeing machine in a continuous dyeing machine; or dyeing treatments performed on the napped surface using roller dyeing, screen dyeing, inkjet dyeing, sublimation dyeing, and vacuum sublimation dyeing. Among these, liquid dyeing using a liquid dyeing machine is preferred for obtaining a soft hand feel and for quality or grade.

[0178] The surface area mass of the composite artificial leather of the present invention is determined by JIS L1913:2010 "General Nonwoven Fabrics Test Methods" "6.2 Mass per unit area (ISO method)", preferably setting the surface area mass to 50 g / m². 2 Above and 600 g / m 2 The following is an example of setting the unit area mass of the artificial leather to 50 g / m². 2 The above, and more preferably 80 g / m 2 The above methods yield artificial leather that also possesses a substantial feel and excellent hand texture. Furthermore, by setting the unit area mass of the artificial leather to 600 g / m²... 2 The following, or more preferably, is 500 g / m 2 The following methods can yield softer composites.

[0179] Additionally, the surface can be designed as needed. For example, post-processing treatments such as perforation, embossing, laser processing, ultrasonic welding, and printing can be performed. Of course, it is also preferred that these post-processing treatments be performed on the artificial leather before dyeing.

[0180] (2) The process of making the adhesive resin exist discretely (the process of forming a composite)

[0181] Subsequently, the adhesive resin is discretely distributed between the layers of the artificial leather and the woven fabric a. Thus, a composite is obtained.

[0182] In the manufacturing method of the composite of the present invention, the unit area mass of the woven fabric a in the manufacturing stage of the composite is preferably 50 g / m². 2 Above and 300 g / m 2 Hereinafter, the preferred unit area mass of the woven fabric a is set to 50 g / m². 2 The above, and more preferably 70 g / m 2 The above can be used to create composites with excellent flame retardant properties or high strength. Furthermore, by setting the unit area mass of the woven fabric a to 300 g / m²... 2 The following, or more preferably, is 250 g / m 2 The following can be used to make a composite with excellent softness.

[0183] Furthermore, in this invention, the unit area mass of the woven fabric a during the manufacturing stage of the composite refers to the value measured by JIS L1913:2010 "General Nonwoven Fabrics Test Methods" "6.2 Mass per unit area (ISO method)".

[0184] In the manufacturing method of the composite of the present invention, regarding the tensile strength of the woven fabric a in the manufacturing stage of the composite, the average value of the tensile strength in any two orthogonal directions is preferably 80 N / 5 cm or more and 1500 N / 5 cm or less. With an average tensile strength of 80 N / 5 cm or more, more preferably 100 N / 5 cm or more, and even more preferably 150 N / 5 cm or more, the morphological stability or durability of the composite is excellent, and therefore preferred. Furthermore, with an average tensile strength of 1500 N / 5 cm or less, more preferably 1200 N / 5 cm or less, and even more preferably 1000 N / 5 cm or less, the formability of the composite is excellent.

[0185] Furthermore, in this invention, the tensile strength of the woven fabric a during the manufacturing stage of the composite refers to the value determined by JIS L1913:2010 "General nonwoven fabrics test methods" "6.3.1 Tensile strength and elongation (ISO method)".

[0186] As a method for applying the adhesive to the composite of the present invention, a rotary screen, a blade roller coater, a gravure roller coater, a contact roller coater, and a calendering coater can be used to coat a specified amount. Regarding the coating amount, if a certain precision is required, the hot-melt resin that serves as the adhesive resin can be directly sprayed onto the woven fabric a, or a nonwoven fabric composed of the adhesive resin can be placed on it (however, this is limited to those where the adhesive resin can be discretely present as described above). To achieve a good hand feel as a composite, a rotary screen or a gravure roller coater is preferred, such as... Figures 2-5 The composite is configured in a manner where the adhesive resin is discretely present, as illustrated. This prevents the composite from hardening in feel or decreasing its breathability.

[0187] As a bonding method for the composite of the present invention, when the bonding resin is a wet-curing resin, bonding is promoted by placing it in a suitable temperature and humidity environment (also known as "curing"). Alternatively, when a thermoplastic resin is used as the bonding resin, it is integrated by hot pressing. Hot pressing can be performed using methods such as hot rollers.

[0188] The amount of adhesive resin can vary depending on the surface condition of the woven fabric a or artificial leather that will be bonded, or the type of adhesive resin, but is preferably 2 g / m². 2 Above and 80 g / m 2 The following applies. The amount of the adhesive resin is preferably 2 g / m³. 2 The above, and more preferably 5 g / m 2 The interlayer bonding strength becomes good. On the other hand, the amount of the adhesive resin is preferably 80 g / m³. 2 The following, or more preferably, is 70 g / m 2 The composite material becomes more flexible.

[0189] Interior materials and seats for vehicles

[0190] Because the composite of the present invention is colorless and has good surface quality, feel, strength, or flame retardant properties, it is preferably used in all applications, primarily in clothing, general merchandise, footwear and bags, interior materials for vehicles, seats, substrates for abrasive pads, various abrasive cloths and wiping cloths, and other industrial materials.

[0191] Among these, interior materials for vehicles containing the composite are preferred due to their excellent flame-retardant properties and strength. Such interior materials for vehicles include, for example, those used in automotive parts such as steering wheels, horn switches, gear shift levers, dashboards, instrument panels, glove boxes, floor carpets, floor mats, headliners, sun visors, and auxiliary handles; more preferably, these vehicle parts include the composite. Furthermore, the term "vehicle" in this invention includes vehicles such as automobiles, airplanes, railway vehicles, and ships, primarily horse-drawn carriages or sedan chairs, and rickshaws, and further includes industrial machinery, construction machinery, and agricultural machinery that can be moved by people or animals, such as excavators, cranes, tractors, and combine harvesters.

[0192] Alternatively, seats incorporating the composite material can also perform well in applications requiring flame retardancy and strength, and are therefore equally preferred. More preferably, the composite material comprises at least a portion of the surface material of the headrest, seat surface, armrests, footrests, etc., for example, the portion in direct contact with the occupant. Of course, the seat of the present invention can be used not only for vehicles such as automobiles, airplanes, railway vehicles, and ships, but also for homes, offices, and shops. Furthermore, the term "seat" as used in the present invention also includes chairs, benches, sofas, couches, stools, legless seats, etc.

[0193] Example

[0194] The present invention will now be described in more detail by way of examples, but the present invention is not limited to these examples.

[0195] [Determination methods and processing methods for evaluation]

[0196] In the determination of various physical properties, those not specifically recorded are obtained based on the methods described above.

[0197] (1) Average single fiber diameter (μm) of ultrafine fibers:

[0198] The average single fiber diameter of the ultrafine fibers was determined and calculated using a scanning electron microscope ("VHX-D500 / D510") manufactured by Keyence Corporation, and by the method described above.

[0199] (2) Length of erect hairs (μm):

[0200] The length of the pile on artificial leather was measured and calculated using a scanning electron microscope ("VHX-D500 / D510") manufactured by Keyence Corporation, and by the method described above.

[0201] (3) Thickness (mm):

[0202] The thickness of the composite was measured and calculated using a "gradient thickness gauge H-1A" manufactured by Ozaki Manufacturing Co., Ltd. The thickness of the artificial leather was measured and calculated using the same method.

[0203] (4) Mass per unit area (g / m²) 2 ):

[0204] The mass per unit area of ​​the composite is determined and calculated using the method described above. Furthermore, the mass per unit area of ​​artificial leather and woven fabric a is determined and calculated using the same method as the thickness of the composite.

[0205] (5) Tensile strength (N / 5 cm):

[0206] The tensile strength of the composite was determined and calculated using an Instron Model 3343 tensile testing machine and the method described above. Furthermore, the tensile strength of the artificial leather and woven fabric a was determined and calculated using the same method as the thickness of the composite.

[0207] (6) Weave density (threads / 2.54 cm)

[0208] The weave density of fabric a is determined and calculated using the following method.

[0209] (i) Five test pieces of 6 cm × 6 cm size were randomly selected from the woven fabric a.

[0210] (ii) Count the number of warp and weft yarns present in the 5.08 cm interval.

[0211] (iii) Divide the number of warp and weft yarns within the 5.08 cm interval by 2 to calculate the warp and weft yarn density of each sample. For the arithmetic mean of the five test pieces (yarns / 2.54 cm), round the first decimal place to calculate the yarn density of fabric a.

[0212] (7) The proportion (by mass%) of modified polyacrylonitrile fiber in woven fabric a

[0213] The proportion of modified polyacrylonitrile fibers in woven fabric a is evaluated by the aforementioned dissolution method. Specifically, the method is as follows.

[0214] (i) Three test pieces of 10 cm × 10 cm size were randomly collected from the woven fabric a.

[0215] (ii) The test pieces were immersed in DMF to dissolve the modified polyacrylonitrile fibers, and then dried at 25°C for 24 hours. The mass ratio of the test pieces before and after dissolution was calculated using the following formula. The arithmetic mean (%) of the three test pieces was rounded to the nearest decimal place to calculate the content of modified polyacrylonitrile fibers.

[0216] (Sample mass before dissolution (g) - Sample mass after dissolution and drying (g)) / (Sample mass before dissolution (g)) × 100 ··· (Formula).

[0217] (8) The proportion (by mass) of modified polyacrylonitrile fiber in the composite.

[0218] The proportion of modified polyacrylonitrile fibers in the composite was evaluated and determined by the following methods.

[0219] (i) When evaluating the proportion of modified polyacrylonitrile fibers in the woven fabric a, the weight of the modified polyacrylonitrile fibers calculated as "sample mass before dissolution (g) - sample mass after dissolution and drying (g)" is multiplied by 100, and the unit area mass (g / m²) of the modified polyacrylonitrile fibers is calculated. 2 ).

[0220] (ii) Multiply the value obtained by dividing the unit area mass of the modified polyacrylonitrile fiber by the unit area mass of the composite by 100 to calculate the content (mass%) of the modified polyacrylonitrile fiber in the composite.

[0221] (9) Opening ratio of the complex (%):

[0222] Regarding the aperture ratio of the composite, an electron microscope (e.g., a "digital microscope VHX-1000" manufactured by KEYENCE Corporation) photograph of the composite surface of 20 cm × 20 cm was taken. The area of ​​the opening was calculated using the "area measurement of circle" function, and the ratio relative to the composite surface was calculated. This operation was performed on samples from five locations, and the aperture ratio was calculated by arithmetic mean.

[0223] (10) Flammability of the composite (mm / min):

[0224] The flammability of the composite was evaluated according to the method described above.

[0225] (11) Color patterns of the complex:

[0226] Regarding the color variation of the composite, place the composite on a urethane foam, drop 3 cc of water onto the surface, allow it to air dry, and then observe for any abnormal appearance such as staining on the sample surface. Mark any visually noticeable staining as "present".

[0227] (12) Surface quality of the composite:

[0228] Regarding the surface quality of the composite, a sensory evaluation was conducted on 20 participants, consisting of 10 healthy adult males and 10 healthy adult females. For composites larger than 200 mm square, a five-stage evaluation was performed as described below, with the highest score being considered the surface quality. In this invention, a good level is defined as "level 3 to 5". Furthermore, this evaluation was not performed for Example 5, which has a surface resin layer.

[0229] • Level 5: The surface of the composite feels smooth to the touch, and fingerprints are visible.

[0230] Level 4: An evaluation between Level 5 and Level 3.

[0231] • Level 3: The surface of the composite has a tactile feel of frictional resistance, but fingerprints are visible.

[0232] Level 2: An evaluation between Level 3 and Level 1.

[0233] • Level 1: The surface of the composite has a tactile feel of frictional resistance, and fingerprints are almost invisible.

[0234] (13) The feel of the composite:

[0235] Sensory evaluation was conducted on 20 participants, consisting of 10 healthy adult men and 10 healthy adult women. The composite was cut into 300 mm square pieces, and the tactile sensation when held in the hand was evaluated as follows, with the highest score being considered the overall feel of the composite. Furthermore, in cases of identical scores, the higher score was considered the overall feel of the composite. In this invention, a "good" level is defined as "level 3 or 4".

[0236] Grade 4: Soft and drapey, with a good feel.

[0237] Grade 3: Slightly soft and with good drape, indicating a good hand feel.

[0238] Level 2: Slightly stiff and with poor drape, indicating a poor feel.

[0239] Level 1: Stiff and lacking drape, resulting in a poor feel.

[0240] [Artificial Leather]

[0241] The artificial leather used in the embodiments and comparative examples was manufactured as illustrated in the following manufacturing examples 1-A to 1-D.

[0242] [Manufacturing Example 1-A] (Artificial Leather A)

[0243] (Sea-island type composite fiber)

[0244] Using polystyrene as the sea component and polyethylene terephthalate (PET) with an intrinsic viscosity (IV value) of 0.72 as the island component, a sea-island type composite fiber with a composite ratio of 20% by mass of sea component and 80% by mass of island component, an island number of 16 islands / 1 filament, and an average single fiber diameter of 20 μm was obtained.

[0245] (Entangled sheet)

[0246] The obtained island-type composite fibers were cut into 51 mm length segments to form fiber webs, which were then passed through a carding machine and a cross-laying machine to form a fiber web. The fiber webs were then needle-punched to produce a surface area mass of 550 g / m². 2 A tangled sheet with a thickness of 2.50 mm.

[0247] (Sheet with PVA)

[0248] The entangled sheet obtained as described above is shrunk using hot water at 96°C. Then, an aqueous solution of polyvinyl alcohol (PVA) with a concentration of 5% by mass and a saponification degree of 88% is impregnated in the entangled sheet that has undergone the hot water shrinkage treatment. Next, the sheet is pressed using rollers and dried for 10 minutes using hot air at 125°C to allow PVA migration, thereby obtaining a sheet containing PVA with a PVA content of 45% by mass relative to the sheet mass.

[0249] (Microfiber sheet)

[0250] The obtained PVA-coated sheet, formed by the entanglement of ultrafine fiber bundles, is impregnated in trichloroethylene and subjected to rolling and compression using a mangle. This process is repeated ten times. This process dissolves and removes the marine components (de-margining) and compresses the PVA-coated sheet, thereby obtaining an ultrafine fiber sheet.

[0251] (Sheet with polymer elastomer)

[0252] The ultrafine fiber sheet obtained as described above was impregnated in a DMF solution of polyurethane with an organic solvent as the main component and the concentration of the solid component adjusted to 12% by mass. The polyurethane resin was then coagulated in an aqueous solution of DMF with a concentration of 30% by mass. Finally, it was dried with hot air at 110°C for 10 minutes to obtain a sheet with a thickness of 2.00 mm containing a polymer elastomer.

[0253] <Sheet-like material>

[0254] The sheet with polymer elastomer obtained as described is cut in half along its thickness direction. The half-cut surface (half-cut surface) is then ground using ring sandpaper of grade 240, thereby obtaining a sheet-like material with raised hairs with a thickness of 0.60 mm.

[0255] (Artificial leather)

[0256] The sheet material with raised fibers, obtained as described above, was dyed with black dye at 125°C using a liquid dyeing machine, followed by drying to obtain artificial leather with an average single fiber diameter of 4.4 μm for the extremely fine fibers. The results are shown in Table 1.

[0257] [Manufacturing Example 1-B] (Artificial Leather B)

[0258] On the napped surface of the artificial leather in Example 1-A, a DMF (dimethylformamide) solution of polyurethane, adjusted to a solids concentration of 30%, is applied by gravure coating and dried to form a 10 g / m² solution. 2 The surface resin layer, except otherwise, is used to obtain artificial leather in the same manner as in Manufacturing Example 1-A. The results are shown in Table 1.

[0259] [Manufacturing Example 1-C] (Artificial Leather C)

[0260] The entangled sheet of manufacturing Example 1-A is set to have a unit area mass of 450 g / m². 2 After manufacturing a sheet with a polymer elastomer and a thickness of 1.50 mm, a sheet with a thickness of 0.45 mm and pile was then manufactured. Otherwise, artificial leather was obtained in the same manner as in Example 1-A. The results are shown in Table 1.

[0261] [Manufacturing Example 1-D] (Artificial Leather D)

[0262] The entangled sheet of Manufacturing Example 1-A was changed to the following entangled sheet: a sheet with a thickness of 2.30 mm containing a polymer elastomer was manufactured, followed by a sheet with a thickness of 0.90 mm and pile. Otherwise, artificial leather was obtained in the same manner as in Manufacturing Example 1-A. The results are shown in Table 1.

[0263] (The entangled sheet of Example 1-D)

[0264] The fiber web is sandwiched between layers of a woven fabric (fabric b) made of polyethylene terephthalate yarns with an intrinsic viscosity (IV value) of 0.72, where the single fiber diameter of the yarns is 10 μm in both the warp and weft directions, the twist is 2500 T / m, and the weave density is 95×76 (warp × weft) per 2.54 cm (1 inch). This results in a layered state of woven fabric / fiber web / woven fabric, which is then needle-punched to produce a unit area mass of 700 g / m². 2 It is an entangled sheet with a thickness of 3.00 mm.

[0265] [Table 1]

[0266]

[0267] [Knitted fabric a]

[0268] Regarding the woven fabric a used in the embodiments and comparative examples, the following examples 2-A to 2-F illustrate this.

[0269] [Manufacturing Example 2-A] (Woven Fabric aA)

[0270] The following woven fabric a was obtained. The results are shown in Table 2.

[0271] Warp 1:

[0272] • Spindle of modified polyacrylonitrile fiber with a Limiting Oxygen Index (LOI) of 32 (referred to as “MOD” in Table 2)

[0273] • Short fiber fineness: 1.7 dtex

[0274] • Fiber length of short fibers: 38 mm

[0275] • Yarn fineness: 295 dtex

[0276] • Number of twists: 15 times / 2.54 cm

[0277] Warp 2:

[0278] • Polyethylene terephthalate multifilaments (referred to as "PET" in Table 2)

[0279] • Monofilament fineness of the long fiber: 3.1 dtex

[0280] • Number of monofilaments in multifilament (filament count): 96

[0281] • Total fineness of multifilament: 330 dtex

[0282] Weft yarn 1:

[0283] • Modified polyacrylonitrile fiber yarn (MOD) with an LOI value of 32

[0284] • Short fiber fineness: 1.7 dtex

[0285] • Fiber length of short fibers: 38 mm

[0286] • Yarn fineness: 295 dtex

[0287] • Number of twists: 15 times / 2.54 cm

[0288] Weft yarn 2:

[0289] Polyethylene terephthalate (PET) multifilament

[0290] • Monofilament fineness of the long fiber: 3.1 dtex

[0291] • Number of monofilaments in multifilament (filament count): 96

[0292] • Total fineness of multifilament: 330 dtex; Weave structure:

[0293] A plain weave structure formed by interlacing warp 1 and warp 2 at a density ratio of 100:0 (using only warp 1), and weft 1 and weft 2 at a density ratio of 50:50.

[0294] • Weave density: Warp direction: Weft direction = 74 yarns / 2.54 cm : 58 yarns / 2.54 cm

[0295] Other features:

[0296] • Mass per unit area: 170 g / m² 2 .

[0297] [Manufacturing Example 2-B] (Woven Fabric aB)

[0298] The weave structure of Manufacturing Example 2-A was changed to the following weave structure, and the woven fabric a was obtained in the same manner as in Manufacturing Example 2-A. The basis weight is 165 g / m². 2 The results are shown in Table 2.

[0299] Weaving structure:

[0300] • Plain weave structure formed by interlacing weft yarn 1 and weft yarn 2 at a density ratio of 80:20.

[0301] [Manufacturing Example 2-C] (Woven Fabric aC)

[0302] The weave structure of Manufacturing Example 2-A was changed to the following weave structure, and the woven fabric a was obtained in the same manner as in Manufacturing Example 2-A. The basis weight is 173 g / m². 2 The results are shown in Table 2.

[0303] Weaving structure:

[0304] • Plain weave structure formed by interlacing weft yarn 1 and weft yarn 2 at a density ratio of 5:95.

[0305] [Manufacturing Example 2-D] (Woven Fabric aD)

[0306] The weave structure of Manufacturing Example 2-A was changed to the following weave structure, and the woven fabric a was obtained in the same manner as in Manufacturing Example 2-A. The basis weight is 158 g / m². 2 The results are shown in Table 2.

[0307] Weaving structure:

[0308] • A plain weave structure formed by interlacing weft yarn 1 and weft yarn 2 at a density ratio of 100:0 (using only weft yarn 1).

[0309] [Manufacturing Example 2-E] (Woven Fabric aE)

[0310] The weave structure of Manufacturing Example 2-A was changed to the following weave structure, and the woven fabric a was obtained in the same manner as in Manufacturing Example 2-A. The basis weight is 176 g / m². 2 The results are shown in Table 2.

[0311] Weaving structure:

[0312] A plain weave structure formed by interlacing warp 1 and warp 2 at a density ratio of 0:100 (using only warp 2), and weft 1 and weft 2 at a density ratio of 0:100.

[0313] [Manufacturing Example 2-F] (Woven Fabric aF)

[0314] The warp yarn 1 and weft yarn 1 of Manufacturing Example 2-A are changed to the following warp yarn 3 and weft yarn 3, and the woven fabric a is obtained in the same manner as in Manufacturing Example 2-A. The unit area mass is 190 g / m². 2 The results are shown in Table 2.

[0315] Warp 3:

[0316] • Meso-type polyaramid fiber yarn with an LOI value of 32 (referred to as "MET" in Table 2)

[0317] Weft yarn 3:

[0318] • Meso-type polyaramid fiber yarn (MET) with an LOI value of 32.

[0319] [Table 2]

[0320]

[0321] [Example 1]

[0322] Artificial leather A is used as the artificial leather, and woven fabric aA is used as the woven fabric a. A moisture-curing reactive urethane adhesive with a melt viscosity of 2000 mPa·s at 125°C is used as the adhesive resin. On the side (back side) of the artificial leather A opposite to the napped surface, the adhesive resin is applied using a gravure roller coater. Figure 2 The illustrated pattern (dot pattern, adhesive resin mass per unit area: 10 g / m²) 2 The points (with a center-to-center distance of 1.2 mm) are discretely distributed. Then, the woven fabric aA is layered and clamped between a pair of calendering rollers with the roller surface temperature set to 90°C. The composite is then cured for 24 hours at an ambient temperature of 25°C and a relative humidity of 50%. The results are shown in Table 3.

[0323] [Example 2]

[0324] The composite was obtained in the same manner as in Example 1, except that the fabric aA was changed to fabric aB. The results are shown in Table 3.

[0325] [Example 3]

[0326] The composite was obtained by replacing artificial leather A with artificial leather B, otherwise in the same manner as in Example 2. The results are shown in Table 3.

[0327] [Example 4]

[0328] The composite was obtained in the same manner as in Example 1, except that the fabric aA was changed to fabric aC. The results are shown in Table 3.

[0329] [Example 5]

[0330] The composite was obtained by replacing artificial leather A with artificial leather C, otherwise in the same manner as in Example 1. The results are shown in Table 3.

[0331] [Example 6]

[0332] The composite was obtained by changing artificial leather A to artificial leather D and woven fabric a to woven fabric aD, otherwise in the same manner as in Example 1. The results are shown in Table 3.

[0333] [Example 7]

[0334] Artificial leather A was replaced with artificial leather D. In the resulting composite, an opening was formed by inserting a perforated plate with needles (needle diameter: 1.4 mm, longitudinal spacing: 5 mm, transverse spacing: 5 mm, opening ratio: 12%), thus creating a composite with an opening. Otherwise, the composite was obtained in the same manner as in Example 1. The results are shown in Table 3.

[0335] [Table 3]

[0336]

[0337] [Comparative Example 1]

[0338] By changing fabric aA to fabric aE, the resulting composite has an adhesion amount of guanidine phosphate as a flame retardant of 15 g / m². 2 The mixture was impregnated in an aqueous solution of guanidine phosphate, pressed through a rolling mill, and dried using a dryer. Otherwise, the composite impregnated with the flame retardant was obtained in the same manner as in Example 1. The results are shown in Table 4.

[0339] [Comparative Example 2]

[0340] On the woven aE side of the composite, a flame retardant coating containing 70% by weight of silica-based resin-treated ammonium polyphosphate (manufactured by Wellchem, 28% phosphorus content, 14% nitrogen content) is applied using a screen coating machine. Then, it is dried at 100°C for 7 minutes, setting the dry adhesion of the flame retardant-containing resin to 70 g / m². 2 In addition, composites with a resin containing a flame retardant coated on the back were obtained in the same manner as in Comparative Example 1. The results are shown in Table 4.

[0341] [Comparative Example 3]

[0342] Without laminating the woven fabric aD, a flame retardant coating containing 70% by mass of silica-based resin-treated ammonium polyphosphate (manufactured by Wellchem, 28% phosphorus content, 14% nitrogen content) is applied to the woven fabric a-side of the composite using a screen coating machine. This is followed by drying at 100°C for 7 minutes, with the dry adhesion of the flame retardant-containing resin set at 70 g / m². 2 In addition, a composite with a flame retardant coated on the back was obtained in the same manner as in Example 6. The results are shown in Table 4.

[0343] [Comparative Example 4]

[0344] The composite was obtained in the same manner as in Example 6, except that the fabric aD was changed to fabric aF. The results are shown in Table 4.

[0345] [Comparative Example 5]

[0346] The woven fabric aD is changed to woven fabric aA, and in the process of forming the composite, the moisture-curing polyurethane resin is coated with a roller coating machine to a concentration of 25 g / m². 2 The coating was applied to the entire surface in the same manner as in Example 6, except that the composite was obtained in the same way. The results are shown in Table 4.

[0347] [Table 4]

[0348]

[0349] The composites obtained in Examples 1 to 7 are all free of color variations and, in addition to having good surface quality or feel, also exhibit good strength or flame retardant properties.

[0350] On the other hand, the composite of Comparative Example 1 had color variations and poor surface quality. Furthermore, the composites of Comparative Examples 2, 3, and 5 all had poor tactile feel. The composite of Comparative Example 4 had poor flame retardant properties.

[0351] Explanation of icon numbers

[0352] 1: Complex

[0353] 2: Hair standing on end

[0354] 3: The boundary line between the piled section and other parts (the line connecting the intersection of fibers oriented along the thickness direction and fibers oriented along the surface direction of the artificial leather).

[0355] 4: Arrow indicating the distance from the intersection of fibers oriented along the thickness direction and fibers oriented along the surface direction of the artificial leather to the tip of the pile.

[0356] 5: Artificial leather

[0357] 6: Woven fabric a

[0358] 7: Next, resin

Claims

1. A composite material comprising adjacent layers of artificial leather and woven fabric a, wherein, The artificial leather comprises: Fiber structures comprising a substrate made of extremely fine fibers as structural components; and Polymer elastomers, The woven fabric a comprises modified polyacrylonitrile fibers. Adhesive resin is discretely present between the layers of the artificial leather and the woven fabric a.

2. The composite according to claim 1, wherein, The polyester fiber content in the woven fabric a is more than 5% by mass and less than 50% by mass.

3. The composite according to claim 1 or 2, wherein, The modified polyacrylonitrile fiber in the composite contains more than 20% by mass and less than 50% by mass.

4. The composite according to claim 1 or 2, wherein, The fibrous structure also includes woven fabric b.

5. An interior material for a vehicle, comprising the composite as described in claim 1 or 2.

6. A component for a vehicle, comprising the composite as described in claim 1 or 2.

7. A seat comprising the composite as described in claim 1 or 2.

Citation Information

Patent Citations

  • Flame-retardant leathery sheet base and method for producing the same

    JP2002201574A

  • Artificial leather and method for producing the same

    JP2008133578A

  • Flame retardant artificial leather, method for producing the same, and flame retardant agent for artificial leather

    JP2013227685A